EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES IN SOCIAL SCIENCES SUBJECTS THROUGH THE PICTURE AND PICTURE LEARNING MODEL IN ELEMENTARY SCHOOLS - Lika Nurhan (Teaching and General Education Studies, 2026)
This study aims to determine whether the Picture and Picture model can improve the learning outcomes of elementary school students. The type of research used is classroom action research (CAR). Data collection techniques use Test and documentation techniques. This study consists of 2 cycles with research procedures using the Kemmis & Mc Taggart model which includes planning, implementation, observation, and reflection. The results of this study indicate that there is an increase in Social Studies learning outcomes in fourth-grade students of SDN 6 Srikaton. This is shown in cycles 1 and 2 where in cycle 1 the value increases from 33% to 41% and in cycle 2 students who completed as many as 10 with a percentage of 83% of 12 students. With this it can be said that the Picture and Picture Model is able to improve the learning outcomes of fourth-grade students of SDN 6 Srikaton.